A solar cell, a method of manufacturing the same, and a solar module

CN122995392APending Publication Date: 2026-10-27RISEN ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510523038.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-24
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0004]因此,目前亟需通过改善PVK-HTL/ETL界面缺陷情况,避免载流子传输下降而影响电池效率

Benefits of technology

[0038]本发明具有以下有益效果:本发明提供的太阳能电池中的钙钛矿层表面的孔隙率小于1%,表面的粗糙度小于50nm,孔隙率非常低且表面光滑,不存在现有技术中存在的由于组分挥发带来的表面缺陷问题,能够有效提升PVK-HTL界面的载流子传输效率,有利于提高电池效率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122995392A_ABST
    Figure CN122995392A_ABST
Patent Text Reader

Abstract

The application discloses a solar cell and a preparation method thereof and a solar module, and relates to the technical field of solar cells. The porosity of the perovskite layer surface of the solar cell provided by the application is less than 1%, and the roughness of the surface is less than 50 nm. The porosity is very low, and the surface is smooth. The surface defect problem caused by component volatilization in the prior art does not exist, the carrier transport efficiency of the PVK- HTL interface can be effectively improved, and the cell efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solar cell technology, and more specifically, to a solar cell, a method for its fabrication, and a solar cell module. Background Technology

[0002] In recent years, the application of perovskite materials in the photovoltaic field has been extensively studied. Due to its excellent photoelectric properties, such as tunable bandgap, direct bandgap, high light absorption coefficient, and excellent carrier transport performance, perovskite has become one of the most promising light-absorbing materials for various optoelectronic applications, especially in the photovoltaic field. Through optimization of perovskite material processing and equipment configuration, the power conversion efficiency (PCE) of perovskite solar cells has increased from 3.8% to 26.7% within a few years.

[0003] Currently, the fabrication of the perovskite thin film is a crucial step in the preparation of perovskite solar cells. Much of the reported treatment methods focus on additive engineering; to avoid additive residues, volatile additives are widely used, as they significantly improve cell efficiency. While their secondary crystallization of perovskite is beneficial for lattice reforming, the increased interface defect density caused by volatilization cannot be ignored. Besides the crystallinity and defects of the perovskite itself affecting cell efficiency, the interface conditions between the perovskite layer (PVK), hole transport layer (HTL), and electron transport layer (ETL) are also critical factors influencing device efficiency.

[0004] Therefore, it is urgent to improve the PVK-HTL / ETL interface defects to avoid a decrease in carrier transport and thus affect battery efficiency.

[0005] In view of this, the present invention is proposed. Summary of the Invention

[0006] The purpose of this invention is to provide a solar cell, a method for its fabrication, and a solar module, which aims to improve the surface defects of the perovskite layer and increase the cell efficiency.

[0007] This invention is implemented as follows:

[0008] In a first aspect, the present invention provides a solar cell, the solar cell comprising a perovskite layer, wherein the porosity of the surface of the perovskite layer is less than 1%;

[0009] And / or, the surface roughness of the perovskite layer is less than 50 nm.

[0010] In an optional embodiment, the perovskite material in the perovskite layer is selected from at least one of MAPbI3-based or FAPbI3-based.

[0011] Preferably, the thickness of the perovskite layer is 500 nm-800 nm;

[0012] Preferably, the perovskite layer is prepared by sequentially coating a first precursor liquid and a second precursor liquid, wherein the first precursor liquid does not contain volatile additives and the second precursor liquid contains volatile additives.

[0013] More preferably, the first precursor liquid includes a perovskite material and a solvent, and the second precursor liquid includes the perovskite material, a volatile additive, and a solvent; wherein the volatile additive is selected from at least one of formamidinium acetate, methylamine chloride, and an ammonium salt.

[0014] In an optional embodiment, the system further includes a substrate on which a hole transport layer and a passivation layer are sequentially disposed, with the perovskite layer disposed on the side of the hole transport layer and the passivation layer away from the hole transport layer and the passivation layer.

[0015] An electron transport layer, a passivation layer, and an electrode are sequentially disposed on the perovskite layer.

[0016] Preferably, the hole transport layer and the passivation layer contain a hole transport material and a hole transport passivation material; wherein the hole transport material is selected from at least one of nickel oxide and polytriarylamine;

[0017] Preferably, the hole transport passivation material includes SAM-4P and phenylethylamine iodide;

[0018] Preferably, the substrate is glass.

[0019] In an optional embodiment, the electron transport layer and the passivation layer contain an electron transport passivation material, an electron transport material, and a protective material.

[0020] The electron transport passivation material is selected from at least one of phenylethylamine iodide and PDADI;

[0021] The electron transport material is selected from at least one of PCBM and C60;

[0022] The protective material is selected from at least one of BCP and MgF2.

[0023] In a second aspect, the present invention provides a method for preparing a solar cell, comprising: coating a first precursor liquid without volatile additives onto a substrate having a hole transport layer and a passivation layer, and then coating a second precursor liquid containing volatile additives to form a perovskite layer.

[0024] In an optional embodiment, the first precursor liquid is obtained by mixing perovskite material and solvent, and the second precursor liquid is obtained by mixing perovskite material, volatile additives and solvent.

[0025] The volatile additive is selected from at least one of formamidinium acetate, methylamine chloride, and ammonium salt.

[0026] In an optional embodiment, the perovskite material is selected from at least one of MAPbI3-based or FAPbI3-based materials;

[0027] Preferably, the perovskite material is Cs. 0.05 FA 0.95 PbI3, prepared from CsI, FAI and PbI2, was used to prepare the first precursor fluid. The ratio of the actual amount of PbI2 to the theoretical amount was controlled to be (102-107):100.

[0028] Preferably, the concentration of the perovskite material in the first precursor fluid is 1-1.5 mmol / ml;

[0029] Preferably, in the second precursor fluid, the concentration of the perovskite material is 1-1.5 mmol / ml, and the content of volatile additives is 1%-5% of the perovskite material content.

[0030] Preferably, the solvent is selected from at least one of N,N-dimethylformamide, dimethyl sulfoxide and N-methylpyrrolidone; more preferably, the solvent includes N,N-dimethylformamide and dimethyl sulfoxide, and the volume ratio of N,N-dimethylformamide and dimethyl sulfoxide is 1:(0.8-1.2).

[0031] In an optional embodiment, an antisolvent is added when coating the second precursor fluid, and annealing is performed after coating is completed;

[0032] Preferably, the first precursor liquid and the second precursor liquid are coated by spin coating, and the spin coating thickness of the first precursor liquid is 300nm-350nm, and the spin coating thickness of the second precursor liquid is 300nm-350nm.

[0033] Preferably, the antisolvent is selected from at least one of chlorobenzene and acetonitrile;

[0034] Preferably, the volume ratio of the antisolvent to the second precursor fluid is (100-150):100.

[0035] In an optional embodiment, the process of preparing the hole transport layer and the passivation layer includes: coating a hole transport material onto a substrate, and then coating a hole transport passivation material; preferably, the process of coating the hole transport passivation material includes: first coating SAM-4P and annealing, and then coating phenylethylamine iodide.

[0036] Preferably, the process further includes: preparing an electron transport layer and a passivation layer on the perovskite layer, and then preparing an electrode; the process of preparing the electron transport layer and the passivation layer includes: first coating an electron transport passivation material and annealing it, then coating an electron transport material, and then coating a protective material.

[0037] Thirdly, the present invention also provides a solar energy module, including a solar cell as described in any of the above embodiments or a solar cell prepared by the preparation method provided in any of the above embodiments.

[0038] The present invention has the following beneficial effects: the porosity of the perovskite layer surface in the solar cell provided by the present invention is less than 1%, the surface roughness is less than 50 nm, the porosity is very low and the surface is smooth, and there is no surface defect problem caused by component volatilization in the prior art. It can effectively improve the carrier transport efficiency of the PVK-HTL interface, which is beneficial to improving the cell efficiency.

[0039] It should be added that the present invention uses a buried treatment on the perovskite layer during the perovskite spin coating process. Before coating the precursor liquid containing volatile additives, a precursor liquid of the same system without volatile additives is coated. This can effectively reduce the problem of increased defects caused by component volatilization, effectively improve the carrier transport efficiency of the PVK-HTL interface, and help improve the battery efficiency. Attached Figure Description

[0040] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0041] Figure 1 This is a structural diagram of a solar cell provided in an embodiment of the present invention;

[0042] Figure 2 The graph shows the EQE test results of the un-buried battery in Comparative Example 1.

[0043] Figure 3 The graph shows the EQE test results of the battery in Example 1 that underwent bottom-mounting treatment.

[0044] Figure 4 This is a SEM image of the surface of Comparative Example 1;

[0045] Figure 5 Here is a SEM image of the surface from Example 1;

[0046] Figure 6 The above are IV curves for Comparative Example 1 and Example 1. Detailed Implementation

[0047] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0048] It should be noted that volatile additives are not solvents, but rather components involved in the perovskite formation process. These components volatilize as the temperature rises during annealing, causing the perovskite structure to be reorganized. However, perovskite materials containing volatile additives tend to address the quality issues of the upper interface film during annealing. Consequently, the lower interface layer develops numerous defects due to component volatilization, limiting carrier transport efficiency between PVK and HTL. Furthermore, perovskite surface defects that continue to accumulate and crystallize on the defective substrate increase dramatically, resulting in numerous pores.

[0049] This invention provides a solar cell comprising a perovskite layer with a surface porosity of less than 1% and a surface roughness of less than 50 nm. The perovskite layer has very low surface porosity and a smooth surface, eliminating surface defects caused by component volatilization present in existing technologies. This effectively improves the carrier transport efficiency at the PVK-HTL interface, thus enhancing cell efficiency.

[0050] Specifically, the solar cells provided in the embodiments of the present invention include, but are not limited to, perovskite solar cells and tandem solar cells. The porosity of the perovskite layer surface in the solar cell can be 0.01%, 0.05%, 0.10%, 0.30%, 0.50%, 0.80%, 1.00%, etc.; the roughness of the perovskite layer surface can be 49nm, 45nm, 40nm, 35nm, 30nm, 25nm, 20nm, 15nm, 10nm, 5nm, etc.

[0051] In some embodiments, the perovskite material in the perovskite layer is selected from at least one of MAPbI3-based or FAPbI3-based materials. All of these perovskite materials are suitable as the main raw material for the perovskite layer, resulting in superior battery performance. The thickness of the perovskite layer is 500nm-800nm, such as 500nm, 600nm, 700nm, 800nm, etc.

[0052] In some embodiments, such as Figure 1As shown, the solar cell also includes a substrate, on which a hole transport layer and a passivation layer are sequentially disposed. A perovskite layer is disposed on the side of the hole transport layer and passivation layer away from them. An electron transport layer, a passivation layer, and an electrode are sequentially disposed on the perovskite layer. Due to the very low porosity and smooth surface of the perovskite layer, the carrier transport efficiency of the PVK-HTL interface can be effectively improved.

[0053] The materials of each layer are not limited; for example, the substrate can be glass. The hole transport layer and passivation layer contain a hole transport material and a hole transport passivation material. The hole transport material is selected from at least one of nickel oxide and polytriarylamine, and can be any one or more of the above. The hole transport passivation material includes SAM-4P and phenylethylamine iodide, and can be any one or more of the above.

[0054] Furthermore, the electron transport layer and passivation layer contain an electron transport passivation material, an electron transport material, and a protective material, and all three materials are present in the electron transport layer and passivation layer. Specifically, the electron transport passivation material is selected from at least one of phenylethylamine iodide and PDADI, and can be any one or more of the above; the electron transport material is selected from at least one of PCBM and C60, and can be any one or more of the above; the protective material is selected from at least one of BCP and MgF2, and can be any one or more of the above.

[0055] Specifically, PCBM refers to [6,6]-phenyl-C61-butyric acid methyl ester, a fullerene derivative that can be purchased commercially, such as from Aladdin. BCP represents 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (Bathocuproin), a small organic molecule material that can also be purchased commercially, such as from Aladdin.

[0056] This invention also provides a method for preparing a solar cell; please refer to [link / reference]. Figure 1 The steps are as follows:

[0057] S1. Preparation of hole transport layer and passivation layer

[0058] The materials and processes used to prepare the hole transport layer and passivation layer on the substrate are not limited, and existing methods for preparing the hole transport layer and passivation layer are all applicable to the preparation method provided in the embodiments of the present invention.

[0059] In some embodiments, the process of preparing the hole transport layer and the passivation layer includes: coating a hole transport material onto a substrate to form a hole transport layer, and then coating a hole transport passivation material to form a passivation layer. The hole transport material is selected from at least one of nickel oxide and polytriarylamine (PTAA). The hole transport material can be any one or more of the above; for example, if nickel oxide is used as the hole transport material, a nickel oxide dispersion can be spin-coated.

[0060] In some embodiments, the process of coating a hole transport passivating material includes: first coating SAM-4P and annealing, then coating phenylethylamine iodide (PEAI) to achieve a better passivation effect. SAM-4P refers to a class of self-assembled monolayer materials containing four pyridine rings, and can be commercially available, such as from Aladdin. PEAI can also be commercially available, such as from Aladdin. The annealing temperature can be 95℃-110℃, and the annealing time can be 5min-30min.

[0061] In some embodiments, the substrate can be glass. The substrate is first ultrasonically cleaned and then treated with ultraviolet light before the hole transport material is coated. Ultrasonic cleaning removes impurities from the glass surface, and ultraviolet irradiation increases the hydrophilicity of the glass, making the subsequently spin-coated material adhere better to the glass surface. The ultraviolet irradiation treatment time can be 10-60 minutes.

[0062] S2, Preparation of perovskite layer

[0063] A first precursor liquid without volatile additives is coated onto a substrate having a hole transport layer and a passivation layer to form a non-volatile PVK layer; then a second precursor liquid containing volatile additives is coated onto the substrate to form a volatile PVK layer.

[0064] This invention optimizes the perovskite layer preparation process by first coating a first precursor liquid without volatile additives, and then coating a second precursor liquid containing volatile additives. This avoids the problem of volatile solvents evaporating at the PVK-HTL interface, reshaping the lattice, increasing defects, and thus reducing carrier transport.

[0065] In some embodiments, the first precursor liquid is obtained by mixing and dissolving perovskite material and solvent, and the second precursor liquid is obtained by mixing and dissolving perovskite material, volatile additives and solvent; wherein, the volatile additives are selected from at least one of formamidine acetate, methylamine chloride (MACl) and ammonium salts, and the volatile additives can be any one or more of the above. Appropriate additives can be selected according to the performance requirements of the product. All of the above volatile additives are suitable for the preparation method provided in the embodiments of the present invention, and can effectively reduce the problem of increased defects caused by component volatilization and effectively improve the carrier transport efficiency of the PVK-HTL interface.

[0066] In some embodiments, the perovskite material used in the preparation process is selected from at least one of MAPbI3-based or FAPbI3-based materials. All of these perovskite materials are suitable as the main raw material for the perovskite layer, resulting in superior battery performance. In a preferred embodiment, the perovskite material is Cs. 0.05 FA 0.95 PbI3 is prepared from CsI, FAI, and PbI2, with a 50% ratio of (CsI+FAI) and 50% PbI2, and a CsI:FAI ratio of 5%:95%. When preparing the first precursor solution, the ratio of actual to theoretical PbI2 usage is controlled at (10²-10⁷):100, i.e., a slight excess of PbI2. This ratio can be 10²:100, 10³:100, 10⁴:100, 10⁵:100, 10⁶:100, 10⁷:100, etc. Using a slight excess of PbI2 in the preparation of the first precursor solution helps to better suppress the negative effects caused by residual volatile reagents. When preparing the second precursor solution, the perovskite material CsI... 0.05 FA 0.95 PbI3 can be prepared by adding materials according to the theoretical dosage using conventional methods.

[0067] Furthermore, by adjusting the amount of solvent, the concentration of perovskite material in the first precursor solution is 1-1.5 mmol / ml (e.g., 1.0 mmol / ml, 1.1 mmol / ml, 1.2 mmol / ml, 1.3 mmol / ml, 1.4 mmol / ml, 1.5 mmol / ml, etc.), and the concentration of perovskite material in the second precursor solution is 1-1.5 mmol / ml (e.g., 1.0 mmol / ml, 1.1 mmol / ml, 1.2 mmol / ml, 1.3 mmol / ml, 1.4 mmol / ml, 1.5 mmol / ml, etc.). The content of volatile additives is 1%-5% of the perovskite material content (in molar mass fraction, the content of volatile additives can be 1%, 2%, 3%, 4%, 5%, etc., of the perovskite material content). When the amounts of perovskite material and volatile additives are within the above ranges, the battery can achieve good battery efficiency.

[0068] In some embodiments, the solvent is selected from at least one of N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), and N-methylpyrrolidone (NMP), and the solvent can be any one or more of the above. In a preferred embodiment, the solvent includes N,N-dimethylformamide and dimethyl sulfoxide, and the volume ratio of N,N-dimethylformamide to dimethyl sulfoxide is 1:(0.8-1.2), such as 1:0.8, 1:0.9, 1:1.0, 1:1.1, 1:1.2, etc. N,N-dimethylformamide and dimethyl sulfoxide are readily available and can better dissolve perovskite materials.

[0069] Furthermore, in the process of preparing the first precursor liquid and the second precursor liquid, in order to accelerate the dissolution of the perovskite material, the raw materials can be heated and dissolved at 60℃-80℃ after mixing. The heating temperature can be 60℃, 65℃, 70℃, 75℃, 80℃, etc.

[0070] In some embodiments, an antisolvent is added during the coating of the second precursor liquid. After coating, the mixture is annealed at 140°C-160°C for 0.2h-1.0h. Adding the antisolvent allows the perovskite layer to form a precursor during the coating process, and the perovskite layer is then formed through short-time annealing. Specifically, the annealing temperature can be 140°C, 145°C, 150°C, 155°C, 160°C, etc., and the annealing time can be 0.2h, 0.4h, 0.5h, 0.6h, 0.8h, 1.0h, etc. The antisolvent is selected from at least one of chlorobenzene and acetonitrile, and can be any one or more of these. The volume ratio of the antisolvent to the second precursor liquid is (100-150):100, such as 100:100, 110:100, 120:100, 130:100, 140:100, 150:100, etc.

[0071] In some embodiments, the first precursor liquid and the second precursor liquid can be coated by spin coating. The spin coating thickness of the first precursor liquid is 300nm-350nm, and the spin coating thickness of the second precursor liquid is 300nm-350nm. By better controlling the spin coating thickness of the first and second precursor liquids, the problem of increased defects due to component volatilization can be reduced more effectively.

[0072] Furthermore, when spin-coating the first precursor liquid, the spin-coating speed is controlled at 800 rpm-1500 rpm, such as 800 rpm, 900 rpm, 1000 rpm, 1200 rpm, 1500 rpm, etc.; the spin-coating time is 8 s-15 s, such as 8 s, 10 s, 12 s, 15 s, etc.; the equipment acceleration is adjusted to 1500-2500, such as 2000, so a speed of 6000 rpm can be reached in 3 seconds. When spin-coating the second precursor liquid, the spin-coating speed is controlled at 4000 rpm-6000 rpm, such as 4000 rpm, 4500 rpm, 5000 rpm, 5500 rpm, 6000 rpm, etc.; the spin-coating time is 20 s-40 s, such as 20 s, 25 s, 30 s, 35 s, 40 s, etc., and the anti-solvent can be added dropwise when the spin-coating reaches 15 s-20 s.

[0073] It should be noted that, according to the designed battery structure, the perovskite layer without volatile components is preferentially prepared onto the hole and passivation layers to effectively avoid the increase of interface defects caused by component volatilization. Without this layer structure, not only is carrier transport hindered, but the surface defects of the perovskite, which continues to anneal and crystallize on the defective substrate, will also increase dramatically. Based on the above structure, a perovskite layer with volatile components is spin-coated onto the perovskite layer without volatile components, followed by annealing. This avoids the downward penetration of volatile components and is more conducive to their upward volatilization, optimizing the surface.

[0074] S3. Fabrication of electron transport layer and passivation layer

[0075] The materials and processes used to prepare the electron transport layer and passivation layer on the perovskite layer are not limited, and existing methods for preparing the electron transport layer and passivation layer are all applicable to the preparation method provided in the embodiments of the present invention.

[0076] In some embodiments, the process of preparing the electron transport layer and passivation layer includes: first coating an electron transport passivation material and annealing it, then coating an electron transport material, and finally coating a protective material to protect the battery. The types of electron transport passivation material, electron transport material, and protective material are as described above and will not be repeated here.

[0077] S4. Electrode preparation

[0078] Electrodes are fabricated on the basis of an electron transport layer and a passivation layer. The type of electrode is not limited, such as a silver electrode.

[0079] Specifically, there are no restrictions on the preparation method of the electrode; for example, Ag electrodes can be prepared by vapor deposition.

[0080] It should be noted that, in this embodiment of the invention, a layer of precursor liquid without volatile additives in the same system is pre-spin-coated at low speed before spin-coating the perovskite layer, and then a layer of perovskite precursor liquid containing volatile additives is spin-coated on it. This solves the problem of poor carrier transport at the PVK-HTL interface caused by component volatilization, and achieves a 2% increase in both the maximum and average battery efficiency.

[0081] This invention also provides a solar module, including the solar cell described above, which is used to supply power. The specific form of the solar module is not limited.

[0082] The features and performance of the present invention will be further described in detail below with reference to embodiments.

[0083] Example 1

[0084] This invention also provides a method for fabricating a solar cell, using Cs perovskite material. 0.05 FA 0.95 PbI3 was prepared from CsI, FAI, and PbI2, with a 50 / 50 ratio of (CsI+FAI) and PbI2, and a CsI:FAI ratio of 5%:95%. In preparing the first precursor solution, the actual to theoretical amount of PbI2 was controlled at a ratio of 105:100, i.e., a slight excess of PbI2. In preparing the second precursor solution, the perovskite material CsI... 0.05 FA 0.95 PbI3 can be prepared by adding it according to the theoretical dosage. The preparation process and component concentrations of the first and second precursor solutions are as follows:

[0085] Preparation of the first precursor solution: Weigh CsI, FAI, and PbI2 according to the above proportions, add them to a mixed solution of DMF and DMSO in a 1:1 volume ratio, and heat to dissolve at 70°C. The concentration of the perovskite material in the first precursor solution is 1.5 mmol / ml.

[0086] Preparation of the second precursor solution: Weigh out CsI, FAI, and PbI2 in the above proportions, weigh out FAAc (formamidinium acetate), and add it to a 1:1 volume ratio of DMF and DMSO solution. Dissolve by heating at 70°C. The concentration of the perovskite material in the second precursor solution is 1.5 mmol / ml, and the mass fraction of the volatile additive in the second precursor solution is 5%.

[0087] Please refer to Figure 1 The fabrication process of solar cells is as follows:

[0088] (1) Take an ITO glass with a length and width of 2.5cm×2.5cm and a thickness of 0.3mm, perform ultrasonic cleaning, and then subject it to 20min of ultraviolet irradiation treatment.

[0089] (2) Spin-coat the prepared nickel oxide dispersion (solvent is deionized water, 20 mg / ml) onto ITO glass, 100 μL / each, control the spin-coating speed at 6000 rpm, the spin-coating time at 30 s, and the acceleration at 2000 (recorded as 6000 / 30 / 2000, and also recorded as such below).

[0090] (3) Spin-coat SAM 4P layer, 100μL / each sheet, parameters 4000 / 30 / 2000, and anneal at 100℃ for 10min after spin coating.

[0091] (4) Spin-coating PEAI layer (lower interface layer), 100 μL / each sheet, 6000 / 30 / 2000.

[0092] (5) PVK layer spin coating: First, spin coat the first precursor solution with 1000 / 10 / 2000, then spin coat the second precursor solution with 5000 / 30 / 2000. At the 18th second of the second spin coating, dynamically add 120 μL of chlorobenzene, and anneal at 150 °C for 0.5 h. The spin coating volume of the first precursor solution is 100 μL, and the spin coating thickness is 300 μm; the spin coating volume of the second precursor solution is 100 μL, and the spin coating thickness is 300 μm.

[0093] (6) Spin-coat PEAI (upper interface layer), 80 μL / each sheet, 4000 / 30 / 2000, dynamically added, add 3-4 seconds after startup, and anneal at 100℃ for 10 min after spin coating.

[0094] (7) Spin-coating PCBM layer, 60μL / each sheet, 2000 / 30 / 1500.

[0095] (8) Spin-coating BCP layer, 80 μL / each sheet, 5000 / 30 / 2000.

[0096] (9) Evaporation of Ag electrode.

[0097] Example 2

[0098] This invention also provides a method for fabricating a solar cell, using Cs perovskite material. 0.05 FA 0.95 PbI3 was prepared from CsI, FAI, and PbI2, with a 50 / 50 ratio of (CsI+FAI) and PbI2, and a CsI:FAI ratio of 5%:95%. In preparing the first precursor solution, the actual to theoretical amount of PbI2 was controlled at a ratio of 102:100, i.e., a slight excess of PbI2. In preparing the second precursor solution, the perovskite material CsI...0.05 FA 0.95 PbI3 can be prepared by adding it according to the theoretical dosage. The preparation process and concentration of each component of the first and second precursor solutions are as follows:

[0099] Preparation of the first precursor solution: Weigh CsI, FAI, and PbI2 according to the above proportions, add them to a mixed solution of DMF and DMSO in a 1:1 volume ratio, and heat to dissolve at 60°C. The concentration of the perovskite material in the first precursor solution is 1.0 mmol / ml.

[0100] Preparation of the second precursor solution: Weigh out CsI, FAI, and PbI2 in the above proportions, weigh out FAAc (formamidinium acetate), and add it to a mixed solution of DMF and DMSO at a volume ratio of 1:0.8. Dissolve the solution by heating at 60°C. The concentration of the perovskite material in the second precursor solution is 1.0 mmol / ml, and the mass fraction of the volatile additive in the second precursor solution is 1%.

[0101] Please refer to Figure 1 The fabrication process of solar cells is as follows:

[0102] (1) Take an ITO glass with a length and width of 2.5cm×2.5cm and a thickness of 0.3mm, perform ultrasonic cleaning, and then subject it to 20min of ultraviolet irradiation treatment.

[0103] (2) Spin-coat the prepared nickel oxide dispersion (solvent is deionized water, 20 mg / ml) onto ITO glass, 100 μL / each, control the spin-coating speed at 6000 rpm, the spin-coating time at 30 s, and the acceleration at 2000 (recorded as 6000 / 30 / 2000, and also recorded as such below).

[0104] (3) Spin-coat SAM 4P layer, 100μL / each sheet, parameters 4000 / 30 / 2000, and anneal at 100℃ for 10min after spin coating.

[0105] (4) Spin-coating PEAI layer (lower interface layer), 100 μL / each sheet, 6000 / 30 / 2000.

[0106] (5) PVK layer spin coating: First, spin coat the first precursor solution with 800 / 15 / 2000, then spin coat the second precursor solution with 4000 / 40 / 2000. At the 20s of the second spin coating, dynamically add 150μL of chlorobenzene, and anneal at 140℃ for 1.0h. The spin coating volume of the first precursor solution is 100μL, and the spin coating thickness is 300μm; the spin coating volume of the second precursor solution is 100μL, and the spin coating thickness is 300μm.

[0107] (6) Spin-coat PEAI (upper interface layer), 80 μL / each sheet, 4000 / 30 / 2000, dynamically added, add 3-4 seconds after startup, and anneal at 100℃ for 10 min after spin coating.

[0108] (7) Spin-coating PCBM layer, 60μL / each sheet, 2000 / 30 / 1500.

[0109] (8) Spin-coating BCP layer, 80 μL / each sheet, 5000 / 30 / 2000.

[0110] (9) Evaporation of Ag electrode.

[0111] Example 3

[0112] This invention also provides a method for fabricating a solar cell, using Cs perovskite material. 0.05 FA 0.95 PbI3 was prepared from CsI, FAI, and PbI2, with a 50 / 50 ratio of (CsI+FAI) and PbI2, and a CsI:FAI ratio of 5%:95%. In preparing the first precursor solution, the actual to theoretical PbI2 dosage was controlled at 107:100, meaning a slight excess of PbI2. In preparing the second precursor solution, the perovskite material CsI... 0.05 FA 0.95 PbI3 can be prepared by adding it according to the theoretical dosage. The preparation process and concentration of each component of the first and second precursor solutions are as follows:

[0113] Preparation of the first precursor solution: Weigh CsI, FAI, and PbI2 according to the above proportions, add them to a mixed solution of DMF and DMSO in a 1:1 volume ratio, and heat to dissolve at 80°C. The concentration of perovskite material in the first precursor solution is 1.5 mmol / ml.

[0114] Preparation of the second precursor solution: Weigh out CsI, FAI, and PbI2 in the above proportions, weigh out FAAc (formamidinium acetate), and add it to a mixed solution of DMF and DMSO at a volume ratio of 1:1.2. Dissolve the solution by heating at 80°C. The concentration of the perovskite material in the second precursor solution is 1.5 mmol / ml, and the mass fraction of the volatile additive in the second precursor solution is 5%.

[0115] Please refer to Figure 1 The fabrication process of solar cells is as follows:

[0116] (1) Take an ITO glass with a length and width of 2.5cm×2.5cm and a thickness of 0.3mm, perform ultrasonic cleaning, and then subject it to 20min of ultraviolet irradiation treatment.

[0117] (2) Spin-coat the prepared nickel oxide dispersion (solvent is deionized water, 20 mg / ml) onto ITO glass, 100 μL / each, control the spin-coating speed at 6000 rpm, the spin-coating time at 30 s, and the acceleration at 2000 (recorded as 6000 / 30 / 2000, and also recorded as such below).

[0118] (3) Spin-coat SAM 4P layer, 100μL / each sheet, parameters 4000 / 30 / 2000, and anneal at 100℃ for 10min after spin coating.

[0119] (4) Spin-coating PEAI layer (lower interface layer), 100 μL / each sheet, 6000 / 30 / 2000.

[0120] (5) PVK layer spin coating: First, spin coat the first precursor solution with 1500 / 8 / 2000, then spin coat the second precursor solution with 6000 / 20 / 2000. At the 15th second of the second spin coating, dynamically add 130 μL of chlorobenzene, and anneal at 160℃ for 0.2 h. The spin coating amount of the first precursor solution is 130 μL, and the spin coating thickness is approximately 350 μm; the spin coating amount of the second precursor solution is 130 μL, and the spin coating thickness is approximately 350 μm.

[0121] (6) Spin-coat PEAI (upper interface layer), 80 μL / each sheet, 4000 / 30 / 2000, dynamically added, add 3-4 seconds after startup, and anneal at 100℃ for 10 min after spin coating.

[0122] (7) Spin-coating PCBM layer, 60μL / each sheet, 2000 / 30 / 1500.

[0123] (8) Spin-coating BCP layer, 80 μL / each sheet, 5000 / 30 / 2000.

[0124] (9) Evaporation of Ag electrode.

[0125] Comparative Example 1

[0126] The preparation process of the precursor fluid for preparing the perovskite layer provided in this comparative example is the same as that of the second precursor fluid in Example 1.

[0127] The fabrication process of solar cells is as follows:

[0128] Steps (1)-(4) refer to Example 1.

[0129] Step (5) is as follows: PVK layer spin coating. First, spin coat the precursor fluid containing volatile additives (i.e., the second precursor fluid) once with 1000 / 10 / 2000, and then spin coat the precursor fluid containing volatile additives once with 5000 / 30 / 2000. At the 18th second of the second spin coating, dynamically add 120 μL of chlorobenzene, and anneal at 150℃ for 0.5 h.

[0130] Steps (6)-(9) refer to Example 1.

[0131] Test case

[0132] (1) The photoelectric conversion efficiency of the batteries prepared in Example 1 and the comparative example was tested, and the results are as follows: Figure 2 and Figure 3 As shown. Test methods and conditions: Four-wire IV test and EQE test, maintaining an ambient humidity of 30% and a temperature of 25℃.

[0133] The 400-500nm region corresponds to the photoelectric conversion efficiency at the hole-PVK interface. Comparison using EQE testing clearly shows that in this region, without a buried substrate, the perovskite hole interface experiences significant defects due to lattice inhomogeneity caused by the volatilization of volatile components, leading to a sharp decrease in photoelectric conversion efficiency at the interface (e.g., ...). Figure 2 The photoelectric conversion efficiency of the battery structure after the buried bottom treatment did not show a significant decrease in the 400-500nm region of the perovskite hole interface. Figure 3 Therefore, this battery structure with a pre-coated non-volatile perovskite precursor can effectively avoid the phenomenon of increased interface defects caused by the volatilization of volatile materials and effectively suppress non-radiative recombination at the interface.

[0134] (2) SEM images of the perovskite films prepared in Example 1 and the comparative example were obtained. The results are as follows: Figure 4 and Figure 5 As shown.

[0135] By comparing the SEM surface images, it is clear that the perovskite film in Comparative Example 1 is of very poor quality (e.g., ...). Figure 4 The surface has numerous pores and defects, resulting in low battery efficiency. In contrast, the SEM surface image of Example 1 (e.g.) shows... Figure 5 The perovskite films produced are of high quality, with no voids and are very dense. This is because volatile additives exist as components during the perovskite synthesis process. During annealing, as the temperature rises, these additive components volatilize, leading to component loss and the generation of a large number of defects.

[0136] It should be noted that, due to the spin-coating of a non-volatile homogeneous perovskite layer, the volatilization of volatile structural components in this invention is slowed down, preventing the formation of numerous surface pores due to drastic component escape, resulting in a surface porosity of almost zero. Testing showed that the surface porosity of the perovskite film obtained in Example 1 was less than 1%, while the surface porosity of the perovskite film obtained in Comparative Example 1 was approximately 50%. The surface roughness of the perovskite film obtained in Example 1 was approximately 40 nm, while the surface roughness of the perovskite film obtained in Comparative Example 1 was greater than 100 nm.

[0137] (3) The IV curves of the batteries prepared in Example 1 and the comparative example were tested, and the results are as follows: Figure 6 As shown. Test method and conditions: Four-wire IV test, maintaining an ambient humidity of 30% and a temperature of 25℃.

[0138] The IV curve comparison clearly shows a significant performance difference between the two batteries. The battery with the same system but no volatile PVK layer has higher Voc and Jsc than the blank control group. The battery conversion efficiency η is calculated using the following formula:

[0139]

[0140] FF represents the fill factor, reflecting the squareness of the IV curve; P in P represents the incident light power. in Under certain conditions, increasing Voc and Jsc can help further improve battery conversion efficiency.

[0141] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A solar cell, characterized in that, The solar cell includes a perovskite layer, the porosity of which is less than 1%. And / or, the surface roughness of the perovskite layer is less than 50 nm.

2. The solar cell according to claim 1, characterized in that, The perovskite material in the perovskite layer is selected from at least one of MAPbI3-based or FAPbI3-based. Preferably, the thickness of the perovskite layer is 500 nm-800 nm; Preferably, the perovskite layer is prepared by sequentially coating a first precursor liquid and a second precursor liquid, wherein the first precursor liquid does not contain volatile additives and the second precursor liquid contains volatile additives. More preferably, the first precursor liquid comprises a perovskite material and a solvent, and the second precursor liquid comprises the perovskite material, a volatile additive, and a solvent; wherein the volatile additive is selected from at least one of formamidinium acetate, methylamine chloride, and an ammonium salt.

3. The solar cell according to claim 1, characterized in that, It also includes a substrate, on which a hole transport layer and a passivation layer are sequentially disposed, and the perovskite layer is disposed on the side of the hole transport layer and the passivation layer away from the hole transport layer and the passivation layer. An electron transport layer, a passivation layer, and an electrode are sequentially disposed on the perovskite layer. Preferably, the hole transport layer and the passivation layer contain a hole transport material and a hole transport passivation material; wherein the hole transport material is selected from at least one of nickel oxide and polytriarylamine; Preferably, the hole transport passivation material includes SAM-4P and phenylethylamine iodide; Preferably, the substrate is glass.

4. The solar cell according to claim 3, characterized in that, The electron transport layer and passivation layer contain electron transport passivation material, electron transport material and protective material; The electron transport passivation material is selected from at least one of phenylethylamine iodide and PDADI; The electron transport material is selected from at least one of PCBM and C60; The protective material is selected from at least one of BCP and MgF2.

5. A method for preparing a solar cell according to any one of claims 1-4, characterized in that, The process includes coating a first precursor liquid without volatile additives onto a substrate having a hole transport layer and a passivation layer, and then coating a second precursor liquid containing volatile additives to form the perovskite layer.

6. The preparation method according to claim 5, characterized in that, The first precursor liquid is obtained by mixing perovskite material and solvent, and the second precursor liquid is obtained by mixing the perovskite material, volatile additives and solvent; The volatile additive is selected from at least one of formamidinium acetate, methylamine chloride, and ammonium salts.

7. The preparation method according to claim 6, characterized in that, The perovskite material is selected from at least one of MAPbI3-based or FAPbI3-based; Preferably, the perovskite material is Cs. 0.05 FA 0.95 PbI3, prepared from CsI, FAI and PbI2, was prepared by controlling the ratio of actual amount of PbI2 to theoretical amount of PbI2 to (102-107):100 when preparing the first precursor fluid. Preferably, the concentration of the perovskite material in the first precursor fluid is 1-1.5 mmol / ml; Preferably, in the second precursor fluid, the concentration of the perovskite material is 1-1.5 mmol / ml, and the content of the volatile additive is 1%-5% of the perovskite material content; Preferably, the solvent is selected from at least one of N,N-dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone; more preferably, the solvent includes N,N-dimethylformamide and dimethyl sulfoxide, and the volume ratio of N,N-dimethylformamide to dimethyl sulfoxide is 1:(0.8-1.2).

8. The preparation method according to claim 6, characterized in that, An antisolvent is added when coating the second precursor liquid, and annealing is performed after coating is completed; Preferably, the first precursor liquid and the second precursor liquid are coated by spin coating, wherein the spin coating thickness of the first precursor liquid is 300nm-350nm and the spin coating thickness of the second precursor liquid is 300nm-350nm. Preferably, the antisolvent is selected from at least one of chlorobenzene and acetonitrile; Preferably, the volume ratio of the antisolvent to the second precursor fluid is (100-150):

100.

9. The preparation method according to claim 5, characterized in that, The process of preparing the hole transport layer and passivation layer includes: coating a hole transport material onto a substrate, and then coating a hole transport passivation material; preferably, the process of coating the hole transport passivation material includes: first coating SAM-4P and annealing, and then coating phenylethylamine iodide. Preferably, the process further includes: preparing an electron transport layer and a passivation layer on the perovskite layer, and then preparing an electrode; the process of preparing the electron transport layer and the passivation layer includes: first coating an electron transport passivation material and annealing it, then coating an electron transport material, and then coating a protective material.

10. A solar energy module, characterized in that, This includes the solar cell described in any one of claims 1-4 or the solar cell prepared by the preparation method described in any one of claims 5-9.